The Feminism in God Is Woman by Ariana Grande - PARILOKITA, KADEK SOGE (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 30 No 1 (2023): Maret, 2023)
This study entitled “The Feminism in God is Woman song by Arianna Grande undertaken the problem related to woman empowerment in American social life nowadays. This study aimed to investigate the phrase of Arianna’s lyric in Woman is God song and it’s meaning that representing feminism. Therefore, this study was limited in the song only, included Arianna’s life as the singer. Thus, this study used descriptive qualitative method by intrinsic and extrinsic technique to analyse the data. This study has found that Arianna Grande’s song entitled “God is Woman’ mostly representing the equality and social position between man and woman. It shown that woman has also a special place in American society equal to man.